2022
DOI: 10.3390/proteomes10020016
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Proteomics in Ovarian Cancer: Dawn of a New Era

Abstract: The ability to identify ovarian cancer (OC) at its earliest stages remains a challenge. The patients present an advanced stage at diagnosis. This heterogeneous disease has distinguishable etiology and molecular biology. Next-generation sequencing changed clinical diagnostic testing, allowing assessment of multiple genes, simultaneously, in a faster and cheaper manner than sequential single gene analysis. Technologies of proteomics, such as mass spectrometry (MS) and protein array analysis, have advanced the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(58 citation statements)
references
References 125 publications
0
46
0
Order By: Relevance
“…Thus, noninvasive clinical tests are needed to identify early disease in women, particularly women at higher risk. In pursuit of biomarkers of early disease detection, the field of proteomics has demonstrated the important clinical relevance of ovarian cancer diagnostics because the proteome closely mimics the dynamic state of human cells, tissues, and organs [ 11 ]. Furthermore, advanced proteomics technologies have helped drive our understanding of the human microbiome [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, noninvasive clinical tests are needed to identify early disease in women, particularly women at higher risk. In pursuit of biomarkers of early disease detection, the field of proteomics has demonstrated the important clinical relevance of ovarian cancer diagnostics because the proteome closely mimics the dynamic state of human cells, tissues, and organs [ 11 ]. Furthermore, advanced proteomics technologies have helped drive our understanding of the human microbiome [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…especially severe adverse events, compared with chemotherapy alone ( 56 ). Current development of proteomics technology (mass spectrometry and protein array analysis) has deepened the identification of potential molecular signaling events and the proteomic characteristics of cervical and ovarian cancer, which facilitates the exploration of new therapeutic agents so as to reduce drug-resistance ( 57 ). In this meta-analysis, it was found that the incidence of the adverse events of grade 3 and above in the patients using pembrolizumab was 21.2%, mainly including tolerable liver dysfunction, hypothyroidism, neutropenia, anemia, decreased appetite, fatigue, and fever.…”
Section: Discussionmentioning
confidence: 99%
“…Jak/STAT 3 plays a role in tumor angiogenesis, survival, invasion, and chemoresistance. The inhibition of this pathway is shown to suppress tumor growth and progression [ 41 ]. The following figure illustrates the necroptosis-related signaling pathways ( Figure 1 ).…”
Section: Necroptosismentioning
confidence: 99%